Monitoring COPD patients: systemic and bronchial eosinophilic inflammation in a 2-year follow-up - Pignatti, Patrizia; Visca, Dina; Zappa, Martina; Zampogna, Elisabetta; Saderi, Laura; Sotgiu, Giovanni; Centis, Rosella; Migliori, Giovanni Battista; Spanevello, Antonio (BMC pulmonary medicine, 2024)
Background High blood eosinophils seem to predict exacerbations and response to inhaled corticosteroids (ICS) treatment in patients with chronic obstructive pulmonary disease (COPD). The aim of our study was to prospectively evaluate for 2 years, blood and sputum eosinophils in COPD patients treated with bronchodilators only at recruitment. Methods COPD patients in stable condition treated with bronchodilators only underwent monitoring of lung function, blood and sputum eosinophils, exacerbations and comorbidities every 6 months for 2 years. ICS was added during follow-up when symptoms worsened. Results 63 COPD patients were enrolled: 53 were followed for 1 year, 41 for 2 years, 10 dropped-out. After 2 years, ICS was added in 12/41 patients (29%) without any statistically significant difference at time points considered. Blood and sputum eosinophils did not change during follow-up. Only FEV 1 /FVC at T0 was predictive of ICS addition during the 2 year-follow-up (OR:0.91; 95% CI: 0.83–0.99, p = 0.03). ICS addition did not impact on delta (T24-T0) FEV 1 , blood and sputum eosinophils and exacerbations. After 2 years, patients who received ICS had higher blood eosinophils than those in bronchodilator therapy ( p = 0.042). Patients with history of ischemic heart disease increased blood eosinophils after 2 years [ p = 0.03 for both percentage and counts]. Conclusions Blood and sputum eosinophils remained stable during the 2 year follow-up and were not associated with worsened symptoms or exacerbations. Almost 30% of mild/moderate COPD patients in bronchodilator therapy at enrollment, received ICS for worsened symptoms in a 2 year-follow-up and only FEV 1 /FVC at T0 seems to predict this addition. History of ischemic heart disease seems to be associated with a progressive increase of blood eosinophils.